Tunable optical properties of multiphase ZnO–V2O5 polycrystalline powders. (November 2015) - Senthil Kumar, E.; Bellarmine, F.; Ramanjaneyulu, M.; Deepthi, Divya; Ramachandra Rao, M.S.
Graphical abstract: Abstract: Bright yellow and white-yellow light emitting ZnO–V2 O5 polycrystalline powders are synthesized by engineering zinc oxide and different zinc vanadate phases. Emission characteristics strongly depend on different zinc vanadate phases. The bright yellow emission is originated from the 3 T2 → 1 A1 and 3 T1 → 1 A1 transitions in the VO4 tetrahedra of zinc vanadate phase. White-yellow emission is the combination of blue and green emissions due to native point defects of ZnO and the yellow and red emission from zinc vanadate.